Assessing the impact of information and communication management on institutional performance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Assessing the impact of information and communication management on institutional performance Compte rendu d'un séminaire du CTA qui s'est tenu à Wageningen, Pays-Bas, les 27-29 janvier 1998.